2018
DOI: 10.3390/molecules23071509
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Docking and In Vitro Approaches towards BACE1 and Cholinesterases Inhibitory Effect of Citrus Flavanones

Abstract: Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease, distinctively characterized by senile plaques, neurofibrillary tangles, and synaptic loss, finally resulting in neuronal death. β-Site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1) and cholinesterases have been identified as therapeutic targets for AD, and the discovery of their inhibitors is of critical importance for developing preventive strategies for AD. To discover natural multi-target compounds possessing BACE1, acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Inhibitory activities of these enzymes were related to the presence of phenolics in sacred lotus. The most abundant flavonoid, naringenin, was previously reported to exhibit the IC 50 values of 42.66 µM against AChE and >100 µM against BChE [ 43 ]. The second most abundant flavonoid, quercetin, was determined as a stronger inhibitor with the IC 50 value of 3.60 µM against AChE [ 44 ] and 1.2 times higher IC 50 value against BChE than AChE inhibition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory activities of these enzymes were related to the presence of phenolics in sacred lotus. The most abundant flavonoid, naringenin, was previously reported to exhibit the IC 50 values of 42.66 µM against AChE and >100 µM against BChE [ 43 ]. The second most abundant flavonoid, quercetin, was determined as a stronger inhibitor with the IC 50 value of 3.60 µM against AChE [ 44 ] and 1.2 times higher IC 50 value against BChE than AChE inhibition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics have also been proven to act as BACE-1 inhibitors [ 51 ]. Naringenin was reported to inhibit BACE-1 activity with the IC 50 value of 30.31 µM [ 43 ], while quercetin, a stronger BACE-1 inhibitor, exhibited the IC 50 value of 5.4 µM [ 52 ]. Kaempferol (the IC 50 value of 14.7 µM) and myricetin (the IC 50 value of 2.8 µM) were also reported to effectively inhibit BACE-1 reaction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major flavonoid contained in Kadsura spp. extract, naringenin, has been previously reported to exhibit AChE inhibitory activity with the IC 50 value of 42.66 µM and BChE inhibitory activity with the IC 50 value of over 100 µM [ 51 ]. It has also been suggested that naringenin could introduce neuroprotective effects in an in vivo study, in which naringenin was found to suppress the activity of AChE, resulting in elevated synaptic cholinergic neurotransmitter level, improved cognitive functions, and prevented memory extinction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…BACE-1 is, therefore, another key enzyme for AD progression. Naringenin was previously reported to inhibit BACE-1 activity with the IC 50 value of 30.31 µM [ 51 ]. Additionally, an oral administration of naringenin could also improve memory deficits in an Aβ-induced mouse model of AD [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies for the evaluation of different CA accessions on AChE inhibitory activity that have been done. It has been reported that a glycosidic compound exhibited a potent neuroprotective activity, improved microglial activation and behavioral dysfunction [40]. Previous studies proved that asiatic acid could reduce the level of corticosterone in a rat's brain, which ameliorates the content of monoamine neurotransmitters and increases the function of hypothalamic-pituitary adrenal for its antidepressant effects [41].…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 99%